Recent Advances in Pharmaceutical Cocrystals: From Bench to Market - Kumar Bandaru, Ravi; Rout, Smruti Rekha; Kenguva, Gowtham; Gorain, Bapi; Alhakamy, Nabil A.; Kesharwani, Prashant; Dandela, Rambabu (Frontiers in Pharmacology, 2021)
The pharmacokinetics profile of active pharmaceutical ingredients (APIs) in the solid pharmaceutical dosage forms is largely dependent on the solid-state characteristics of the chemicals to understand the physicochemical properties by particle size, size distribution, surface area, solubility, stability, porosity, thermal properties, etc. The formation of salts, solvates and polymorphs are the conventional strategies to alter the solid characteristics of pharmaceutical compounds but they have their own limitations. Cocrystallization approach was established as an alternative method for tuning the solubility, permeability and processability of APIs by introducing another compatible molecule/s into the crystal structure without affecting its therapeutic efficacy to successfully develop the formulation with the desired pharmacokinetic profile. In the present review, we have grossly focused on cocrystallization, particularly at different stages of development, from design to production. Furthermore, we have also discussed regulatory guidelines to pharmaceutical industries, challenges associated with the design, development and production of pharmaceutical cocrystals with commercially available cocrystal-based products.